ENTEROBACTERIA ISOLATED FROM SYNANTHROPIC FLIES (DIPTERA, CALYPTRATAE) IN MEDELLÍN, COLOMBIA (2015)
Enterobacteria (Enterobacteriaceae) causing enteric diseases can be carried and dispersed through insects that act as mechanical vectors, especially flies (Insecta: Diptera). In this study, enterobacteria associated with synanthropic flies were isolated and identified; four different urban areas in the municipality of Medellín were surveyed. Thirteen taxa of calyptrate flies belonging to four families were identified and classified according to the Mechanical Vector Risk Index (MVRI) value, which is proposed in this study. Chrysomya megacephala (Fabricius, 1794), Lucilia cuprina (Wiedemann, 1819), Chrysomya albiceps (Wiedemann, 1819), and Musca domestica Linnaeus, 1758 are of high risk; Fannia sp., Atherigona orientalis Schiner, 1868, and Ophyra aenescens (Wiedemann, 1830) of moderate risk; remaining species were classified as low or no risk. Escherichia coli was the most frequent bacterium according to the number of isolations (32%), followed by Klebsiella oxytoca (12%), Pasteurella pneumotropica (11%), and Kluyvera spp. (8%). Raoultella ornithinolitica, Stenotrophomponas maltophilia, and Chryseobacterium menigosepticum were isolated for the first time from flies. Finally, 22 new records of bacteria associated with eight fly species were reported. The results allow us to foresee the existence of a generalist pattern in the interaction between flies and bacteria and indicate that synanthropic flies have a quantifiable potential as vectors of infectious diseases according to the index proposed.